Microsoft SQL Server 2000 programming by example - Guerrero, Fernando G. (By example series., 2001)
SQL Server 2000 Programming by Example provides clear and concise examples of basic programming techniques used in SQL Server 2000 primarily using Transact-SQL. Even if you're a complete novice to SQL Server 2000 programming, you will benefit by reading through the book's logical process. SQL Server 2000 is introduced and explored, database structure is designed and built, and finally a variety of programming techniques are studied and reviewed. If you are already familiar with SQL Server 2000 programming, you may use the book as a quick reference guide that provides plenty of pertinent examples.